Edukasi Budidaya dan Pengolahan Jahe Kelompok Proklim Jati Asri Kota Madiun - Widyawati, Paini Sri; Epriliati, Indah; Ristiarini, Susana; Purwanto, Agus; Ganjari, Leo Eladisa; Nugroho, Christianto Adhy (Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Ginger is spice plant that potential to develop to be phytopharmacon because it contains bioactive compounds, such as alkaloid, flavonoid, phenolic, triterpenoid, saponin, and essential oil, i.e., gingerol, shogaol, zingiberene, (+)-curcumene, (-)-β-sesquiphelandrene paradol, and bisabolene. These compounds can used to maintain body health. Proklim Jati Asri oversees the PKK Asman Toga, a community group enthusiastic about growing ginger to preserve the environment and reduce the greenhouse effect. The Proklim program, in partnership with the Faculty of Agricultural Technology, Widya Mandala Catholic University, Surabaya, aims to provide ginger cultivation and processing training to community groups with limited knowledge and skills. This training allows them to cultivate and process ginger into semi-finished and finished products that can generate income, contribute to environmental conservation, and create herbal medicine at home. This activity was held on Tuesday, June 17, 2025, and was attended by 22 participants (women from the PKK Asman Toga). The knowledge evaluation showed a 68,18% of participant increased in theirs’s knowledge. Throughout the activity, participants were highly enthusiastic, collaborated with each other to complete tasks, and actively participated in the training. The community service activity succeeded in improving the participants' abilities in cultivating and processing ginger.